Evidence‐based dentistry can effectively be taught to dental care professional students – A mixed methods study. (28th November 2017) - Kahatab, A. F.; Ho, Y. B.; O'Reilly, D.; Tan, C.; McTernan, J.; Ahmad, T.; O'Halloran, A.; Sagheri, D.; Abdollahi, A.; Mac Giolla Phadraig, C.
Abstract: Background: Little research exists in the teaching of evidence‐based dentistry (EBD) to students in the fields of dental hygiene, dental nursing and orthodontic therapy. This study aims to analyse the effect of a 1‐day EBD programme on knowledge and confidence whilst also gaining insight into students' experience of the intervention. Method: A mixed methods study was utilised with explanatory sequential design. The population consisted of dental hygiene (DH), dental nursing (DN) and orthodontic therapy (OT) students (N = 44). The intervention consisted of a 1‐day active learning EBD programme, delivered via group projects and lectures. In the initial quantitative phase, a standardised questionnaire pre‐ and post ‐intervention measured changes in confidence for all participants, whilst change in knowledge was measured for DH and OT students only. Following this, focus groups were scheduled for all members of each discipline 3 months post‐intervention for DN and 2 months post‐intervention for DH and OT students. Semi‐structured focus group schedules were drawn up, and groups organised according to the outcomes of quantitative data analysis. Qualitative results were analysed using a deductive adaptation of Burnard's thematic content analysis. Results: Forty‐two students took part (94.45%) in this study. Median knowledge scores increased from zero to two of five ( P  < .001), whilst median confidence score doubled from four to eight of eight ( P  < .001). Results of thematic content analysis were coincident with quantitative results; however, it also provided constructive feedback regarding design and content of the course. Conclusions: A 1‐day bespoke programme in EBD increased students' confidence and knowledge in EBD skills. However, the findings further suggest that two successive half‐day training sessions instead of one full‐day training, tied in with coursework that requires the application of the acquired skills, may increase the learning experience further.